Quality of Work life Affecting Quiet Quitting of the Teachers Under The Secondary Educational Service Area Office, Nakhon Pathom - Jai-dee, Phisanu; Buasuwan, Prompilai; Suebnusorn Klaijumlang, Wanwisa (Suan Dusit Graduate School Academic Journal, 2025)
This research aimed to study (1) the level of quality of work life and quiet quitting, (2) the relationship between quality of work life and quiet quitting, and (3) the factors of quality of work life that influenced quiet quitting. The research employed a survey methodology, with the sample comprising 340 teachers of the Secondary Educational Service Area Office, Nakhon Pathom. The sample size was determined using Yamane’s formula, and stratified random sampling was employed, using schools as strata with equal proportions. A 5-rating scale questionnaire in the form of a checklist with an overall reliability score of 0.923 was used for data collection. Data were analyzed by using statistical methods, including mean, percentage, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. The findings revealed that 1) the overall OWL of government teachers under the Secondary Educational Service Area Office, Nakorn Pathom was at the low level, while their quiet quitting behavior was at the high level 2) there was a negative correlation between QWL and quiet quitting at the statistical significance level of .01 3) QWL factors, including opportunities for self-development, organizational management, social responsibility and organizational belonging, and work-life balance, significantly influenced quiet quitting. These factors collectively predicted 15.70% of the variance in quiet quitting at the statistical significance level of .05.